Enhancement of multi-wavelength brillouin-erbium fibre laser utilizing fibre Bragg Grating filter - Abdul Rashid, Hairul Azhar; Yusoff, Zulfadzli; Mohd Nasir, M. N.; Al-Mansoori, M. H.; Choudhury, Pankaj Kumar (IEEE, 2008)
We demonstrate an efficient multi-wavelength Brillouin-erbium fibre laser incorporating an FBG filter. The self-lasing effect is reduced and subsequently the number of output channels increased. Furthermore, the stability of output channels is also improved.